Exogenous re-infection by a novel Streptococcus pneumoniae serotype 14 as a cause of recurrent meningitis in a child from The Gambia - Antonio, Martin (BioMed Central, 2009)
We report a case of an infant who experienced exogenous re-infection of Streptococcus pneumoniae serotype 14 as a cause of recurrent meningitis after apparently successful antibiotic treatment with ceftriaxone. eBURST analysis revealed that isolates from the two episodes of meningitis belonged to hypervirulent ST63 and ST3321 clonal complexes respectively.